Retinal structure and function in vigabatrin‐treated adult patients with refractory complex partial seizures. (1st September 2016) - Sergott, Robert C.; Johnson, Chris A.; Laxer, Kenneth D.; Wechsler, Robert T.; Cherny, Katya; Whittle, JoAnn; Feng, Ge; Lee, Deborah; Isojarvi, Jouko
Summary: Objective: Evaluate visual‐field and retinal‐structure changes following adjunctive vigabatrin treatment in vigabatrin‐naive adults with refractory complex partial seizures (rCPS). Methods: Prospective, longitudinal, single‐arm, open‐label study (NCT01278173). Eligible patients (≥2 seizures/month who failed ≥3 therapies) who could reliably perform perimetry (Humphrey automated static) and retinal‐structure assessment (spectral‐domain optical coherence tomography) prior to vigabatrin exposure. Following vigabatrin initiation, testing occurred within 1 month (reference) and 3, 6, 9, and 12 months. End points included mean change from reference in mean deviation (dB) and average retinal nerve fiber layer (RNFL) thickness, visual‐acuity changes from baseline, and number of patients who met predefined vision‐parameter changes at two (confirmed) or three (persistent) consecutive visits. Results: Sixty‐five of 91 screened patients received ≥1 vigabatrin dose (all‐patients‐treated set [APTS]); 55 had valid reference and ≥1 post–reference assessments (full‐analysis set [FAS]). Thirty‐six APTS patients with valid pre–/post–reference values completed all planned visits (per‐protocol set [PPS]). Thirty‐eight (59%) APTS patients completed the study; 27 (42%) withdrew (none for visual‐field changes); 32% and 15% had abnormally thin RNFL and abnormal visual acuity at baseline, respectively; 20% had abnormal central 30 degree visual fields in the reference period. No significant mean near visual‐field changes were observed (PPS); mean change in average RNFL thickness increased significantly (1‐year data: Left‐eye: 6.37 μm, confidence interval (CI) 4.66–8.09; right‐eye: 7.24 μm CI 5.47–9.01; PPS). No confirmed three‐line decreases in visual acuity (FAS) were observed; five patients had predefined confirmed/persistent visual‐field changes (FAS). All vision‐related adverse events were nonserious; the most common was vision blurred (9%). Significance: Prior to vigabatrin initiation, rCPS patients may already exhibit vision deficits. Up to 1 year of adjunctive vigabatrin treatment did not significantly change population near visual fields. Five patients met predefined visual‐field‐change criteria. RNFL thickening of unknown clinical significance was observed. Limitations include single‐arm, open‐label design; patients' inability to perform ophthalmic/visual‐field examinations; and limited vigabatrin‐exposure duration.